A Coplanar Transmission Line High-T/sub c/ Superconductive Oscillator at 6.5 GHz on a Single Substrate - Klieber, Ralf; Ramisch, Roland; Valenzuela, Alejandro; Weigel, Robert; Russer, Peter (IEEE Microwave and Guided Wave Letters, 1992)
The design and construction of a planar, low-noise cryogenic oscillator operating at 6.5 GHz are presented. The oscillator has been built as a hybrid superconductive microwave integrated circuit (SMIC) on a single 10*10 mm LaAlO/sub 3/ substrate. Single-sided, coplanar line structures are used throughout the circuit with YBa/sub 2/Cu/sub 3/O/sub 7- delta / as conductor material. The oscillator was constructed around a GaAs MESFET as the active device. The complete oscillator is cooled by immersion in liquid nitrogen. An output power of 4.9 dBm was obtained. Single-sided noise power at 10 kHz offset from carrier was -90 dBc/Hz.<>
elib2cris::1512001600,klieber1992
Keywords: barium compounds; Conducting materials; Coplanar transmission lines; Microwave oscillators; single substrate; SHF; MESFET; GaAs